Bioactive Glass: Hierarchically Nanoporous Bioactive Glasses for High Efficiency Immobilization of Enzymes (Adv. Funct. Mater. 15/2014). (April 2014) - He, Wen; Min, Dandan; Zhang, Xudong; Zhang, Yang; Bi, Zhiying; Yue, Yuanzheng
<x xml:space="preserve">Abstract</x> A hierachically nanoporous bioactive glass is developed by X. D. Zhang, Y. Z. Yue, and co‐workers, which is used for effectively immobilizing enzymes to enhance their catalytic activity. The image illustrates the catalysis mechanism of the immobilized enzyme. The novel nanostructure is expected to be utilized as a solid support for any enzyme for bioconversion, bioremediation, biosensors, and drugs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>